A comparison of DAS and geophones for VSP acquisition at a dedicated field laboratory - Correa, J.; Dean, T.; Van Zaanen, L.; Tertyshnikov, Konstantin; Pevzner, R.; Bona, A. (2017)
Distributed Acoustic Sensing (DAS) is a novel technology that uses fibre-optic cables to detect acoustic signals. DAS provides a cost-effective solution for acquiring vertical seismic profile (VSP) surveys, but it suffers from a comparatively poor signal-to-noise ratio and uncertainties in depth. In this work, we compare the quality of a VSP survey acquired using a permanently installed fibre-optic DAS system with that acquired using a conventional 3-component geophone system. The results show that DAS is capable of producing a time-depth curve with differences of less than 0.8 ms from the geophone results but that the raw interval velocities calculated from the DAS data fluctuate wildly due to their small depth interval. The datasets themselves were consistent although the S/N of the DAS data was inferior and small differences in phase were evident. The DAS amplitudes were also found to decay with cosine-squared of the incidence angle compared to cosine for the geophone data. Corridor stacks generated from both datasets were broadly consistent but residual noise in the DAS data contaminated the stack. The results of this, and previously published surveys, should encourage the more widespread use of DAS for zero offset VSPs.